2022
DOI: 10.1073/pnas.2111294119
|View full text |Cite
|
Sign up to set email alerts
|

Full adoption of the most effective strategies to mitigate methane emissions by ruminants can help meet the 1.5 °C target by 2030 but not 2050

Abstract: Significance Agricultural methane emissions must be decreased by 11 to 30% of the 2010 level by 2030 and by 24 to 47% by 2050 to meet the 1.5 °C target. We identified three strategies to decrease product-based methane emissions while increasing animal productivity and five strategies to decrease absolute methane emissions without reducing animal productivity. Globally, 100% adoption of the most effective product-based and absolute methane emission mitigation strategy can meet the 1.5 °C target by 203… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
111
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 171 publications
(113 citation statements)
references
References 64 publications
1
111
0
1
Order By: Relevance
“…A detailed description of the methods and results of the meta-analysis discussed here can be found in Arndt et al (2022). Briefly, the database used for the analysis included treatment means from in vivo stud-ies published from 1964 to 2018.…”
Section: A Review Of the Arndt Et Al (2021) Meta-analysismentioning
confidence: 99%
See 3 more Smart Citations
“…A detailed description of the methods and results of the meta-analysis discussed here can be found in Arndt et al (2022). Briefly, the database used for the analysis included treatment means from in vivo stud-ies published from 1964 to 2018.…”
Section: A Review Of the Arndt Et Al (2021) Meta-analysismentioning
confidence: 99%
“…Daily CH 4 emissions were analyzed in 783 mean comparisons, yCH 4 in 598, and iCH 4 in 260. The analysis also examined the effect of mitigation strategies on DMI, milk production (or daily gain), and total-tract NDF digestibility but these results are not discussed here (see Arndt et al, 2022). Analyses were run across all ruminant species and included main mitigation strategies and their respective subcategories as potential moderator fixed effects.…”
Section: A Review Of the Arndt Et Al (2021) Meta-analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Many articles reviewed the scientific literature on enteric methane mitigation options (Hristov et al, 2013a;Knapp et al, 2014;Negussie et al, 2017;Beauchemin et al, 2020;Lassen and Difford, 2020). Arndt et al (2022) recently conducted a meta-analysis to examine 98 enteric methane mitigation options from a comprehensive data set of treatment means from 425 peer-reviewed studies published between 1963 and 2018. They found that most of the options (63 out of 98, or 64%) were not successful in mitigating enteric methane.…”
Section: Introductionmentioning
confidence: 99%